Analisis Tingkat Kebangkrutan Pada Perusahaan Asuransi Yang Terdaftar Di Bursa Efek Indonesia - Mikha Novalina Sinaga; Frendy A. O. Pelleng; Joanne V. Mangindaan (Universitas Sam Ratulangi, 2019)
The purpose of this research study is to determine the result of prediction analysis of potential bankruptcy on eleven insurance companies sector which has been listed in Indonesia Stock Exchange year 2015 to 2018. Bankruptcy is a condition when a company experiences insufficient funds to run its business. Bankruptcy is uncertainty about the ability of a company to continue its operations if the financial condition held has decreased. In fact, not all companies experience financial management problems that often lead to bankruptcy. Based on the result and conclusions of the analysis using Altman Z-Score method that: in 2015-2018 there were several companies that were safe, namely: PT. Bina Dana Arta Insurance Tbk, PT. Harta Aman Pratama Insurance Tbk, PT. Jasa Tania Insurance Tbk, PT Indonesian reinsurance airline Tbk, PT. Panin Insurance Tbk, PT. Panin Financial Tbk, PT Victoria Insurance Tbk. Then there are companies that in 2015- 2017 are healthy but in 2018 in prone conditions, namely: PT. Bintang Insurance Tbk,and PT. Multi Artha Guna Insurance Tbk, but different from PT. Mitra Maparya Insurance Tbk which in 2015 was in vulnerable condition but in 2016-2018 is safe. And PT. Ramayana from 2015-2018 is in vulnerable condition.